Search for the rare decays B→πℓ+ℓ- and B0→ηℓ+ℓ- - Lees, Jean-Pierre; Adametz, Aleksandra; Uwer, Ulrich (Physical review. D, Particles, fields, gravitation, and cosmology, 2013)
We present the results of a search for the rare flavor-changing neutral-current decays B→πℓ+ℓ− (π=π±, π0 and ℓ=e, μ) and B0→ηℓ+ℓ− using a sample of e+e−→Υ(4S)→B¯¯¯B decays corresponding to 428 fb−1 of integrated luminosity collected by the BABAR detector. No significant signal is observed, and we set an upper limit on the isospin and lepton-flavor averaged branching fraction of B(B→πℓ+ℓ−)<5.9×10−8 and a lepton-flavor averaged upper limit of B(B0→ηℓ+ℓ−)<6.4×10−8, both at the 90% confidence level. We also report 90% confidence level branching fraction upper limits for the individual modes B+→π+e+e−, B0→π0e+e−, B+→π+μ+μ−, B0→π0μ+μ−, B0→ηe+e−, and B0→ημ+μ−.
Im Titel ist das Pluszeichen "+", das Minuszeichen "-" und die Zahl "0" hochgestellt
Gesehen am 23.11.2021